The local radio-galaxy population at 20 GHz - Sadler, E.; Ekers, Ronald; Mahony, E.; Mauch, T.; Murphy, T. (2014)
We have made the first detailed study of the high-frequency radio-source population in the local Universe, using a sample of 202 radio sources from the Australia Telescope 20 GHz (AT20G) survey identified with galaxies from the 6dF Galaxy Survey (6dFGS). The AT20G-6dFGS galaxies have a median redshift of z = 0.058 and span a wide range in radio luminosity, allowing us to make the first measurement of the local radio luminosity function at 20 GHz. Our sample includes some classical Fanaroff-Riley type I (FR I) and FR II radio galaxies, but most of the AT20G-6dFGS galaxies host compact (FR 0) radio active galactic nuclei which appear to lack extended radio emission even at lower frequencies. Most of these FR 0 sources show no evidence for relativistic beaming, and the FR 0 class appears to be a mixed population which includes young compact steep-spectrum and gigahertz peaked-spectrum radio galaxies. We see a strong dichotomy in the Wide-field Infrared Survey Explorer (WISE) mid-infrared colours of the host galaxies of FR I and FR II radio sources, with the FR I systems found almost exclusively in WISE 'early-type' galaxies and the FR II radio sources in WISE 'late-type' galaxies. The host galaxies of the flat- and steep-spectrum radio sources have a similar distribution in both K-band luminosity and WISE colours, though galaxies with flat-spectrum sources are more likely to show weak emission lines in their optical spectra. We conclude that these flat-spectrum and steep-spectrum radio sources mainly represent different stages in radio-galaxy evolution, rather than beamed and unbeamed radio-source populations. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.